The role of oxidative stress levels and S100B levels in children with functional neurological disorder: Pediatric functional neurological disorder - Sizer, Esra; Çobanoğlu, Tuğba; Kaplan, İbrahim (Journal of Surgery and Medicine, 2023)
Background/Aim: Although stressors and traumatic life events are known to be predisposing factors for developing functional neurological disorder (FND), the etiology of the disorder has not been fully elucidated. In this study, oxidative stress parameters and serum levels of S100B protein were investigated in pediatric patients with functional neurological disorder. The association of these parameters with stress factors and traumatic life events was investigated. Methods: This case-control study included a control group of 35 patients aged 8-18 years and 32 healthy subjects diagnosed with functional neurological disorder. The Childhood Trauma Scale and Dissociative Experiences Scale were applied to both groups. Serum levels of the patient and control groups were compared by blood sampling: total oxidant status (TOS), total antioxidant status (TAS), oxidative stress index (OSI), and S100B. Results: It was found that the Childhood Trauma Scale total score, emotional neglect, emotional abuse, physical neglect and the Dissociative Experiences Scale were statistically significantly higher in the FND group than in the control group (P˂0.001, P˂0.001, P=0.013, P=0.017, P˂0.001). Stressors were found to be statistically significantly higher in the FND group than in the control group (P=0.020). There was no statistical difference between the FND group and control groups regarding the TAS, TOS, OSI, and S100B levels (P=0.965, P=0.228, P=0.268, P=0.517, respectively). Conclusion: Our study is the first to investigate TOS, TAS, OSI and S100B in children with FND. In our study, although stressors and traumatic experiences were significantly higher in the functional neurological disorder group compared to the control group according to the stress susceptibility model, contrary to expectations, there was no significant difference in oxidative stress parameters and serum S100B levels. It was thought that the interaction between FND, which is characterized by biopsychosocial interaction and can manifest itself with various clinical symptoms, and stress may not be linear as initially thought, and the interaction between genetic predisposition and environmental factors may play a more complex role. The absence of significant differences observed in oxidative stress parameters and serum S100B levels may suggest that we should focus on different pathways and different potential biomarkers that need to be investigated in the future to understand the etiology and diagnosis of FND. However, the limitations noted above may affect the generalizability of the study findings.